Analysis of the Factors Influencing Cash Holding in Corporation - Subing, Hesty Juni Tambuati; Yalin, Felita Linta (SAN Scientific, 2023)
This study examines the effect of net working capital, leverage, and cash flow on cash holding in the Pharmaceutical Industry Sub-Sector corporation listed on the Indonesia Stock Exchange (IDX) in 2016-2020. This study uses a sample of pharmaceutical industry sub-sector companies listed on the Indonesia Stock Exchange (IDX). The sampling technique in this study used purposive sampling and obtained a sample of 9 companies. This study uses secondary data, namely financial statements obtained from the Indonesian Stock Exchange (IDX) official website. The analytical method used is a panel data regression model with the EViews 10. The results of this study indicate that only the Net Working Capital variable does not affect Cash Holding. In contrast, the other independent variable does not affect Cash Holding, while the other independent variables used in this study have an effect. This research is used to provide an overview to companies that cash holding policies are good for companies and provide an overview as a reference for consideration in making investment decisions by taking into account the impact of making cash holding decisions by companies